Oxidative Dearomatization and Sigmatropic 1,3-Acyl Shift in Excited State: Aromatics to Embellished cis-Hydrindanes - Sahu, Raghaba; Singh, Vishwakarma (Synthesis, 2019)
A stereoselective synthetic route to embellished cis-hydrindanes from simple aromatic precursors is described. Oxidative dearomatization, ring expansion, and photochemical 1,3-acyl shift are the key features of our approach. Oxidative dearomatization of o-(hydroxymethyl)phenols followed by π4s + π2s cycloaddition furnishes bicyclo[2.2.2]octanes with contiguous keto epoxide groups, which upon ring expansion lead to bicyclo[3.2.2]nonanes endowed with a β,γ-enone chromophore. Unbridging of bicyclo[3.2.2]nonanes upon singlet excitation furnishes embellished cis-hydrindanes.
Keywords: oxidative dearomatization; cycloaddition; 1,3-acyl shift; cis-hydrindanes; ring expansion